Optical Absorption Microspectroscopy (μ-OAS) Based on Schwarzschild-Type Cassegrain Optics. Issue 4 (April 2015) - Chassé, Mathieu; Lelong, Gérald; van Nijnatten, Peter; Schoofs, Ivo; de Wolf, Jürgen; Galoisy, Laurence; Calas, Georges
A new experimental setup, combining a custom-designed Schwarzschild-type Cassegrain-based microscope and an ultraviolet-visible-near infrared (UV-Vis-NIR) spectrophotometer, has been developed, focusing the light beam down to 20 μm diameter. Optical absorption spectra (in the 300–2500 nm range) have been measured on micrometer-sized natural glass inclusions providing information on iron speciation in magmatic melts. The absence of contribution from the host crystal matrix provides a test of the efficiency of micro-focusing. A microthermometric stage has been adapted on the microscope for measuring optical absorption spectra up to 900 K with application to the thermochromism of minute natural spinel crystals (MgAl2 O4 :Fe 2+, Cr 3+ ). This experimental setup provides an easy and fast way to follow the evolution of spectral properties and color of glasses or crystals with temperature as well as the possibility of measuring spatially resolved optical absorption spectra.